Ӵук тӧл: кылбуръёс, сонет тугоко, берыктэмъёс / Иосиф Бобров - Бобров Иосиф Петрович (Удмуртия, 1993)
Экземпляры: (20230714) / Инвентарный номер: 22967 / Цена: 75.00 / Сис.шифр: 84(2=664.1Удм) / Авт.знак: Б 72 / ГРНТИ: 17 / ББК: 84(2=664.1Удм)